Experimental Investigation on BN-Based Flexible Composite Phase-Change Material for Battery Module - Tang, Xianwen; Deng, Jian; Wu, Zixin; Li, Xinxi; Wang, Changhong (Frontiers in Energy Research, 2022)
This study aims toward the application of composite phase-change material (CPCM) in electric vehicles, which suffers from leakage, high rigidity, and low thermal conductivity. In this study, a novel flexible composite phase-change material (CPCM) with high thermal conductivity and low leakage has been proposed, presented, and utilized in a battery module. Among these, polyethylene glycol (PEG), as a phase-change component, styrene–butadiene–styrene (SBS) as support material, and ethylene–propylene–diene monomer (EPDM) as assisted packaging material could greatly enhance the flexibility and deformability of CPCM. Besides, boron nitride (BN) was adopted to enhance the heat-dissipating capacity and reduce the temperature difference in the module. In addition, compared with other cooling methods, the battery module with compact and efficient advantages are analyzed at different discharge rates. The results revealed that the flexible CPCM was controlled below 44.8°C, and the temperature difference was maintained within 5.6°C at 3C discharge rate. Even during the charge–discharge cycles, it displayed lower temperature fluctuation within the acceptable range. These outstanding shape recovery and antileakage performances of BN-based flexible CPCM would provide insights into battery modules with desirable assembly methods and process flexibility.